Middle East Oil Show 2003
DOI: 10.2118/81567-ms
|View full text |Cite
|
Sign up to set email alerts
|

Asphaltene Precipitation in High Gas-Oil Ratio Wells

Abstract: Asphaltene deposits have been observed in a number of high gas-oil ratio (GOR) wells in north Ghawar. Even though the oil reservoir is undersaturated two small gas-caps are present as a result of gas injection during the 1960s and 1970s. New development wells drilled recently to produce oil and gas from the gas-cap areas have experienced asphaltene deposition. The cause of precipitation is the stripping of the asphaltenes from the crude by the gas. This paper describes the results of an inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…Asphaltene problems have been treated mechanically, chemically, and/or operationally. Among available remedies in each technology that have been widely applied in the world (Jamaluddin et al 1996;Avila et al 2001;Kokal et al 2003;Wang and Civan 2005;Hamid 2006;Al-Ghazi and Lawson 2007;Frost et al 2008), the most conventional ways have been applied in our target fi eld. The selection of remedial action was based on operational and cost reasons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asphaltene problems have been treated mechanically, chemically, and/or operationally. Among available remedies in each technology that have been widely applied in the world (Jamaluddin et al 1996;Avila et al 2001;Kokal et al 2003;Wang and Civan 2005;Hamid 2006;Al-Ghazi and Lawson 2007;Frost et al 2008), the most conventional ways have been applied in our target fi eld. The selection of remedial action was based on operational and cost reasons.…”
Section: Introductionmentioning
confidence: 99%
“…The increase of asphaltene risks through gas injection has been recognized as a general rule (Kokal et al 2003;Srivastava et al 1999;Parra-Ramirez et al 2001;Sarma 2003;Jamaluddin et al 2000;Kokal et al 2004;Negahban et al 2005;Okwen 2006; Moghadasi et al 2006). A preparatory evaluation of asphaltene behavior under gas-mixing conditions is important to minimize risks and to optimize the gas-injection project.…”
Section: Introductionmentioning
confidence: 99%
“…One inclusion within a quartz overgrowth in the 1610e1613 m contains a yellow fluorescence oil with brown solid organic matter (bitumen) and has a Q G/B of 1.57, the largest amount of CO 2 (around 10 mol%), the lowest methane content (around 5%) and a high CH 2 /CH 3 ratio. They are interpreted as being produced by the deasphalting of the irreducible oil during the accumulation of the gas, a process commonly observed in other petroleum reservoirs (Milner et al, 1977;Lomando, 1992;Hwang et al, 1998;Kokal et al, 2003). Bitumen, also observed between detrital grains in Zone 1 (Fig.…”
Section: Alteration Of Residual Oil By Interaction With Gas In a Gas mentioning
confidence: 75%
“…They used the deposition data from aerosols (deposition rates for aluminum and iron particles in air) to verify their model. Kocabas et al [22] Kokal et al [23] described the results of the study on oil samples of north Ghawar reservoir that started to show precipitation problem and ways to alleviate the deposition problem. They reported that the precipitation was linked to gas coning/cresting in the wells.…”
Section: Asphaltene Depositionmentioning
confidence: 99%